The effect of home-based intervention program on body composition, VO2 max and vital capacity among sedentary females leaving in unstable country - Soh, Kim Geok; Noori, Jian Abdullah; Soh, Kim Lam; Ong, Swee Leong; M. N., Mohad Anizu; M. K., Siswantoyo (Wolters Kluwer - Medknow Publications and Media, 2021)
The aim of this study is to investigate whether a home-based physical activity and dietary awareness intervention program could improve on body composition, VO2max and vital capacity among sedentary females leaving in an unstable country. The intervention program was conducted for 12-weeks and consisted of two groups which were experimental and control groups. Total subjects selected in this study were 44 and was equally distributed for both groups. Body Composition was measured using the equation of BMI and skinfold thickness. While VO2max and Vital Capacity were measured using step test and Jaeger Spirometer, respectively. Data was collected three times i.e. baseline pre-test, post-test1, and post-test2, but only the experimental group participants received the intervention program. Results reported that there were significant improvements in body mass index, body fat, VO2max and vital capacity as compared to controls group. The reported t values were, respectively. As the conclusion, home-based physical activity and dietary intervention program can positively influence sedentary undergraduate female students’ physiological variables especially in term of improving the VO2max capability.